2021
DOI: 10.1016/j.jpeds.2020.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Public Health Ethics into Shared Decision Making for Children During the Novel Coronavirus Disease-19 Pandemic

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Restricting visitation is necessary from a public health perspective but can have unintended but deleterious consequences [ 28 ] as patients and their families are in a state of heightened psychological distress owing to the lethality of the SARS-CoV-2 virus [ 29 ]. In line with existing literature, we identified that patients are isolated and distressed and restricted families are having to navigate the shared decision-making process differently [ 30 , 31 ]. The COVID-19 pandemic has also placed a heavy toll on healthcare professionals, who grappled with fatigue while navigating unfamiliar virtual modalities (to connect competent patients with their loved ones), cared for their own colleagues who fell ill, and comforted dying, isolated patients [ 32 ].…”
Section: Discussionsupporting
confidence: 64%
“…Restricting visitation is necessary from a public health perspective but can have unintended but deleterious consequences [ 28 ] as patients and their families are in a state of heightened psychological distress owing to the lethality of the SARS-CoV-2 virus [ 29 ]. In line with existing literature, we identified that patients are isolated and distressed and restricted families are having to navigate the shared decision-making process differently [ 30 , 31 ]. The COVID-19 pandemic has also placed a heavy toll on healthcare professionals, who grappled with fatigue while navigating unfamiliar virtual modalities (to connect competent patients with their loved ones), cared for their own colleagues who fell ill, and comforted dying, isolated patients [ 32 ].…”
Section: Discussionsupporting
confidence: 64%
“…25 Any long-term strategy for control of COVID-19 will need to include plans for universal vaccination of children with the involvement of pediatric health care providers. 26 One also needs to consider many of the challenges to the logistics of trying to vaccinate most of the domestic and global population. Moderna has never had an approved vaccine before, and neither has BioNTech.…”
Section: What Comes Next? Is the Pandemic Over?mentioning
confidence: 99%
“…However, different countries have different rules for the need to adolescents' consent for vaccination. Nonetheless, physicians can have a supportive role in helping them decide, as they can consult, give information and transparent the benefits of being vaccinated against SARS‐CoV‐2, encouraging the adolescent to consent voluntarily 67 …”
Section: Introductionmentioning
confidence: 99%